Experimental investigation on EV battery cooling and heating by heat pipes - Wang, Q.; Jiang, B.; Xue, Q.F.; Sun, H.L.; Li, B.; Zou, H.M.; Yan, Y.Y. (Elsevier, 2015)
Enhancing battery safety and thermal behaviour are critical for electric vehicles (EVs) because they affect the durability, energy storage, lifecycle, and efficiency of the battery. Prior studies of using air, liquid or phase change materials (PCM) to manage the battery thermal environment have been investigated over the last few years, but only a few take heat pipes into account. This paper aims to provide a full experimental characterisation of heat pipe battery cooling and heating covering a range of battery ‘off-normal’ conditions. Two representative battery cells and a substitute heat source ranging from 2.5 to 40 W/cell have been constructed. Results show that the proposed method is able to keep the battery surface temperature below 40 °C if the battery generates less than 10 W/cell, and helps reduce the battery temperature down to 70 °C under uncommon thermal abuse conditions (e.g. 20–40 W/cell). Additionally, the feasibility of using sintered copper-water heat pipes under sub-zero temperatures has been assessed experimentally by exposing the test rig to −15 °C/−20 °C for more than 14 h. Data indicates that the heat pipe was able to function immediately after long hours of cold exposure and that sub-zero temperature conditions had little impact on heat pipe performance. We therefore conclude that the proposed method of battery cooling and heating via heat pipes is a viable solution for EVs.